Toxic Acetaminophen Exposure Induces Distal Lung ER Stress, Proinflammatory Signaling, and Emphysematous Changes in the Adult Murine Lung. (28th November 2019) - Sandoval, Jeryl; Orlicky, David J.; Allawzi, Ayed; Butler, Brittany; Ju, Cynthia; Phan, Caroline T.; Toston, Roy; De Dios, Robyn; Nguyen, Leanna; McKenna, Sarah; Nozik-Grayck, Eva; Wright, Clyde J.
Abstract : Clinical studies have demonstrated a strong association between both acute toxic exposure and the repetitive, chronic exposure to acetaminophen (APAP) with pulmonary dysfunction. However, the mechanisms underlying this association are unknown. Preclinical reports have demonstrated that significant bronchiolar injury occurs with toxic APAP exposure, but very little information exists on how the distal lung is affected. However, cells in the alveolar space, including the pulmonary epithelium and resident macrophages, express the APAP-metabolizing enzyme CYP2E1 and are a potential source of toxic metabolites and subsequent distal lung injury. Thus, we hypothesized that distal lung injury would occur in a murine model of toxic APAP exposure. Following exposure of APAP (280 mg/kg, IP), adult male mice were found to have significant proximal lung histopathology as well as distal lung inflammation and emphysematous changes. Toxic APAP exposure was associated with increased CYP2E1 expression in the distal lung and accumulation of APAP-protein adducts. This injury was associated with distal lung activation of oxidant stress, endoplasmic reticulum stress, and inflammatory stress response pathways. Our findings confirm that following toxic APAP exposure, distal lung CYP2E1 expression is associated with APAP metabolism, tissue injury, and oxidant, inflammatory, and endoplasmic reticulum signaling. This previously unrecognized injury may help improve our understanding of the relationship between APAP and pulmonary-related morbidity.